South Pole Ice Core Sea Salt and Major Ions ... - Winski, Dominic A. (U.S. Antarctic Program (USAP) Data Center, 2023)
This dataset includes all major ion chemistry data from the South Pole Ice Core as well as sea salt sodium data resampled at annual resolution. The development of this dataset is discussed in Winski et al. 2021. The chloride, nitrate, sulfate, magnesium and calcium data have not yet been published, nor has any data prior to the Holocene. Please contact the dataset authors if you have questions. ...